PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN IPAS DI KELAS V SD SANTO THOMAS 2 MEDAN - Yehezkiel Fajar Lihardo Sinaga; Juliana; Reflina Sinaga; Ester J Simarmata; Eka Margaret Sinaga; Patri Janson Silaban (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of the Project Based Learning model on students’ learning outcomes in Science and Social Studies (IPAS), particularly on the topic of the Human Respiratory System, at Grade V of SD Santo Thomas 2 Medan in the 2025/2026 academic year. The research employed an experimental method with a quantitative approach. The instrument used to collect data consisted of 30 test items. The sample comprised 28 students selected through purposive sampling technique.To assess students’ initial abilities, a pretest was administered, yielding an average score of 63.43. The posttest results showed an improvement compared to the pretest, with the students’ average score increasing to 82. The improvement in learning outcomes was supported by the correlation coefficient test results, where rcount ≥ ttabel (0.949 ≥ 0.374). Furthermore, hypothesis testing was conducted by comparing tcount ≥ ttabel, resulting in 15.348 ≥ 2.056. Based on these findings, Ha was accepted and Ho was rejected. It can be concluded that the Project Based Learning model has a significant effect on students’ learning outcomes in Science and Social Studies (IPAS) at Grade V of SD Santo Thomas 2 Medan.